2x+7=x+29

Simple and best practice solution for 2x+7=x+29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7=x+29 equation:


Simplifying
2x + 7 = x + 29

Reorder the terms:
7 + 2x = x + 29

Reorder the terms:
7 + 2x = 29 + x

Solving
7 + 2x = 29 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
7 + 2x + -1x = 29 + x + -1x

Combine like terms: 2x + -1x = 1x
7 + 1x = 29 + x + -1x

Combine like terms: x + -1x = 0
7 + 1x = 29 + 0
7 + 1x = 29

Add '-7' to each side of the equation.
7 + -7 + 1x = 29 + -7

Combine like terms: 7 + -7 = 0
0 + 1x = 29 + -7
1x = 29 + -7

Combine like terms: 29 + -7 = 22
1x = 22

Divide each side by '1'.
x = 22

Simplifying
x = 22

See similar equations:

| c(2x-d)=4c | | 3-x+7=19 | | .4w-11=-3 | | 4(5r+45)= | | 2,236,000+(-17.740x)=3,500,000 | | a^2-3ax+2ap-6=0 | | 5(x-3)=2(x-5) | | 11*i=0 | | 6(53+x)=x+2 | | 1/3(x-6)=4x-2/5(2-x) | | 53+x=6(x+2) | | 10+3y=90 | | 5x-19-3=-7 | | 3x=1x-6 | | 2(1+2x)=-6+3x | | 2x+56+4x-2=90 | | -a^2-6a=0 | | 2x+25=90 | | i-3=0 | | 76=y+48 | | 3i-4=0 | | 8x+r= | | -s^2+15s=0 | | 7x-9+5x+3=54 | | -b^2-13b=0 | | 1/5-10=-25 | | -17x+17=119 | | -2w=70 | | 2(2y-1)=3y+10 | | x-2+4x=6x-9 | | x^3-7x^2-2x-40=0 | | 9x-10+4(x-1)=90 |

Equations solver categories